PERAN MEDIASI KEPUASAN PELANGGAN PADA PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN (STUDI PADA PELANGGAN PT. PELITA AIR SERVICE DENPASAR) - Dewa Ayu Dwi Indra Swari; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (VALUES, 2024)
Pelita Air Service Denpasar is an airline company that faces tight competition in the national aviation industry, so it needs to increase customer satisfaction and loyalty which can be formed through service quality and appropriate priceperceptions. This research aims to determine the role of customer satisfaction in mediating the influence of service quality andprice perception on customer loyalty. This research uses a quantitative approach with an associative design. The sample taken was 100 respondents with a sampling technique using purposive sampling, so that the respondents were customers of PT. PelitaAir Service Denpasar. The data collection method in this research isquestionnaires. The analysis technique used is path analysis. The results of this research show that 55.2% of the variation in customer loyalty of PT. Pelita Air Service Denpasar is influenced by service quality, price perception and customer satisfaction. Based on hypothesis testing in path analysis, the resultsobtained are: (1) service quality and price perception have a positive effect on customer satisfaction; (2) service quality, priceperception, and customer satisfaction have a positive effect on customer loyalty; (3) customer satisfaction is able to mediate the influence of service quality and price perception on customer loyalty at PT. Pelita Air Service Denpasar.